2016
DOI: 10.1186/s12984-016-0196-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of hip extension assistance during loaded walking with a soft exosuit

Abstract: BackgroundRecent advances in wearable robotic devices have demonstrated the ability to reduce the metabolic cost of walking by assisting the ankle joint. To achieve greater gains in the future it will be important to determine optimal actuation parameters and explore the effect of assisting other joints. The aim of the present work is to investigate how the timing of hip extension assistance affects the positive mechanical power delivered by an exosuit and its effect on biological joint power and metabolic cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 49 publications
6
117
0
Order By: Relevance
“…Recent work with hip and ankle exoskeletons has focused on the goal of reducing the metabolic cost of walking, and researchers have succeeded in a number of experiments (Ronsse et al, 2011; Mooney et al, 2014; Ding et al, 2016a,b; Ruiz Garate et al, 2016; Seo et al, 2016). Research groups have used both rigid exoskeletons (Ruiz Garate et al, 2016), as we use in our experiment, and soft exoskeletons to test the effect of different hip assistance strategies on metabolic output (Ding et al, 2016a; Panizzolo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work with hip and ankle exoskeletons has focused on the goal of reducing the metabolic cost of walking, and researchers have succeeded in a number of experiments (Ronsse et al, 2011; Mooney et al, 2014; Ding et al, 2016a,b; Ruiz Garate et al, 2016; Seo et al, 2016). Research groups have used both rigid exoskeletons (Ruiz Garate et al, 2016), as we use in our experiment, and soft exoskeletons to test the effect of different hip assistance strategies on metabolic output (Ding et al, 2016a; Panizzolo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate mappings between these underlying models can cause reduction in performance and increase in the frequency and magnitude of errors due to confusion, distraction, and concerns for safety [37], [38]. Zhang et al [39] and Ding et al [40] have shown that different control methods and timings of active assistance altered human performance. It may be that certain control mappings better align with the operator's mental model across goals or behaviors, yielding improved performance and the ability to develop improved skill-based behaviors.…”
Section: A Mental Modelsmentioning
confidence: 99%
“…As previously mentioned, the less the user must directly input and control, the better for synergy and ability to engage with the surroundings. However, the selection of the underlying controller impacts the kinematics and metabolic consumption (e.g., [40], [58]- [60]). The actuation timings are important for enabling efficient mode transitions such that systems do not have a sluggish response or disturb the desired biomechanics.…”
Section: Automation Mode Confusion and System Trustmentioning
confidence: 99%
“…Moreover, assistance of the hip joint also may improve gait in amputees, because assisted hip motion was found to not only improve spatiotemporal gait parameters, i.e. velocity, cadence, step time, stance time, swing time, double support time, stride length and spatial asymmetry in stroke survivors [13], but also to reduce the metabolic cost during walking in healthy subjects [14].…”
Section: Introductionmentioning
confidence: 99%